Histidine metabolism after Bretschneider cardioplegia in cardiac surgical patients - Teloh, J. K; Ansorge, L; Petersen, M; Demircioglu, E; Waack, I. N; Brauckmann, S; Jakob, H; Dohle, D.-S (Physiological research, 2018)
Bretschneider (histidine-tryptophan-ketoglutarate) solution with its high histidine concentration (198 mM) is one of many cardioplegic solutions, which are routinely used for cardiac arrest. The aim of this study was to evaluate the physiological biochemical degradation of administered histidine to histamine and its major urinary metabolite N-methylimidazole acetic acid. A total number of thirteen consecutive patients scheduled for elective isolated coronary artery bypass grafting with cardiopulmonary bypass were enrolled in the prospective observational designed study at the Department of Thoracic and Cardiovascular Surgery between 04/2016 and 06/2016. Patients received 1.7 l Bretschneider solution on average. Before and at the end of operation as well as in the postoperative course, urine samples gathered from the urinary catheter bag were analyzed. During the operative period, urinary histidine concentration significantly increased from 29 micromol/mmol creatinine to 9,609 micromol/mmol creatinine. Postoperatively, histidine excretion reduced while histamine as well as N-methylimidazole acetic acid excretion rose significantly. Patients showed elevated levels of histidine, histamine as well as N-methylimidazole acetic acid in urine, but no unmanageable hemodynamic instability possibly arising from the histamine's biological properties. Chemically modified histidine might reduce uptake and metabolization while maintaining the advantages of buffer capacity.
Keywords: Female; Mannitol; Histidine; Cardiac Surgical Procedures; Postoperative Period; ženské pohlaví; Hemodynamics; hemodynamika; kardiopulmonální bypass; lidé; Histamine; kardiochirurgické výkony; chlorid draselný; Cardiopulmonary Bypass; kardioplegické roztoky; mannitol; pooperační období; Middle Aged; Cardioplegic Solutions; histamin; prospektivní studie; Male; Aged; Prospective Studies; glukosa; histidin; Glucose; Procaine; koronární bypass; lidé středního věku; senioři; mužské pohlaví; prokain; Potassium Chloride; Coronary Artery Bypass; Humans